Implementing a Reminder System in the Northern Part of Belgium to Stimulate Postpartum Screening for Glucose Intolerance in Women with Gestational Diabetes: The “Sweet Pregnancy” Project - Katrien Benhalima; Sabine Verstraete; Frederik Muylle; Katelijn Decochez; Roland Devlieger; Paul Van Crombrugge; Ann Verhaegen; Johan Wens; Chantal Mathieu (International Journal of Endocrinology, 2017)
Aims. To evaluate the feasibility and efficacy of a gestational diabetes (GDM) recall register on the long-term screening uptake postpartum and to evaluate the prevalence of prediabetes postpartum. Methods. Evaluation of a GDM recall register implemented in 66 obstetrical centers in the northern part of Belgium from 2009 to 2016. Registrants receive yearly reminders to have a fasting plasma glucose test in primary care to timely detect prediabetes. Results. After 6 years, 7269 women were registered. The yearly response rates varied from 74.4% after the first year to 61.8% after the fifth year. The number of women who reported a screening test varied from 67.4% after the first year to 71.9% after the fifth year. Compared to women who responded at least once to a reminder, women who never responded were more often <30 years (41.4% versus 33.9%, p<0.001) and were more often obese (29.3% versus 20.8%, p≤0.001). Over a period of 6 years, 7.3% (CI 6.0%–8.8%) developed diabetes and 27.4% (CI 23.9%–31.0%) developed impaired fasting glycaemia. Conclusion. We show now the long-term feasibility and efficacy of a GDM recall register to stimulate screening postpartum. One-third of women developed prediabetes within 6 years.